Sýnisbók þess að Ïsland er ekki barbaraland - Jón Þorkelsson 1697-1759 (Stofnun Árna Magnússonar í íslenskum fræðum, 2022)
Specimen Islandiæ non barbaræ written in latin by Jón Þorkelsson (1697-1759). It counts the literary works written in Iceland set out to prove that Iceland and indeed Icelanders are not barbaric at all. The book is bilingual and edited by Margrét Eggertsdóttir and Guðvarður Már Gunnlaugsson. This is volume nr. 109 in the series Rit Árnastofnunar.
Keywords: Geschichte 1740-1750; Literatur; Kultur; Island; Quelle